Exploration of Changes in the Character of Curiosity and Discipline of Students in the Puberty Phase (Case Study at MIS Bakti, Padang City) - Kamilah An Shoriah; Hendrizal Hendrizal; Wahyuni Mulya Helmi (Journal of Educational Sciences, 2026)
Puberty is a critical developmental phase characterized by biological, psychological, and social changes that influence students' character development. During this period, curiosity and discipline often undergo significant changes that affect learning behavior. This study aimed to explore changes in students' curiosity and discipline during puberty at MIS Bakti, Padang City, and to examine the roles of teachers, parents, and peers in shaping these character changes. A qualitative case study approach was employed involving two students in the puberty phase as the primary participants, supported by teachers and parents as key informants. Data were collected through classroom observations, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing with verification. The findings revealed that both students experienced a shift in curiosity from academic learning toward social and emotional interests, particularly curiosity related to interpersonal relationships. This shift was accompanied by declining discipline, reflected in reduced learning focus, violations of school dress regulations, and decreased compliance with school rules. The findings also showed that teachers, parental guidance, and peer interactions played decisive roles in either supporting or hindering the development of students' curiosity and discipline during puberty. The study concludes that effective character development during puberty requires consistent collaboration among schools, families, and peers to channel students' curiosity into positive learning experiences while strengthening discipline.